The Approach of Finland and Sweden to the Soviet and Nazi Occupations of the Baltic States in 1940–1944. - Stalmokaitė , Ignė (Genocidas ir rezistencija, 2012)
The rapid change in the status of the Baltic States at the beginning of the 1940s, led to erratic and mixed reactions of the outside world, while the struggle of dependent nations for their statehood established a certain place for the Baltic States in the international community. The study analyses the attitude of two Nordic countries – Sweden and Finland – to the three countries that lost their independence during the period of the first two occupations in 1940–1944. So far, historians have not analysed this topic. Looking back on this relatively recent period of history, which was particularly difficult for the Baltic States, and at the position of the Nordic countries would allow to better assess cooperation opportunities of the countries of the Baltic Sea region arising in the twenty-first century and determine the importance of the Baltic States in cross-border relations in the Baltic Sea region. The aim of the study is to analyse in detail the official position of Finland and Sweden, and the attitudes of their peoples towards the Baltic States during the period of the first two occupations. The key focus of the study is analysis of the problem of recognition of the Soviet occupation and the annexation of the Baltic States by the Nordic countries. An important part of the analysis involves the study of the correspondence of Lithuanian diplomats working in the Nordic countries: this would allow a better understanding of public sentiment in Finland and Sweden regarding the two occupational regimes in the Baltic countries. The first part of the article deals with the official approach of the Finnish and Swedish governments towards Soviet occupation and annexation of the Baltic States. The analysis of the sources, political reasoning, historiography of Lithuania and foreign countries, and the press of the Nordic countries reveals that Sweden recognised the incorporation of Lithuania, Latvia and Estonia into the Soviet Union de facto by signing several agreements with Moscow. Meanwhile, Finland, due to unfavourable relations with the Soviet Union, was reluctant to give an assessment of the changed status quo of the Baltic States. The Finnish government maintained a policy of tacit non-recognition of the annexation of the Baltic States. The second part of the study explores the approach of the Nordic countries towards the Nazi occupation of the Baltic States. Finland and Sweden treated the Nazi actions in the east of the Baltic Sea region as a result of the unpredictable progress of WWII. A certain interest in the problems of the occupied Baltic States on the part of Swedish and Finnish society is revealed by publications in the Nordic press. They question the fate of the three Baltic States in a fragmented manner. The last part of the study examines the approach of the Nordic countries towards the three occupied Baltic States on the basis of correspondence of Lithuanian diplomats residing in the Nordic countries. After the Soviet occupation these Lithuanian diplomats stayed in the Nordic countries and assessed public opinions prevailing in Sweden and Finland towards the occupation. The study reveals that in Sweden, in June 1940, the actions of the Soviet Union in Lithuania, unlike those in Latvia and Estonia, were not treated as occupational. The fellow feelings expressed by representatives of the Swedish government to the Baltic States were personal in nature and did not affect the official position of Sweden. Between 1941 and 1944, Finnish society was also friendly to the three Baltic States. This was expressed in negative statements against the occupation of the Baltic States carried out by the Soviet Union. The Finnish and Swedish press paid only fragmentary attention to the issue of enforcement and change of occupational regimes in the east of the Baltic Sea region.